Private Vocational Processing Training Into Economic Valued Products as One of The Companies for Entrepreneurs for Mgmp Chemistry Teachers of Padang City - Melindra wanda Mulia (Fakultas MIPA Universitas Negeri Padang, 2021)
Entrepreneurship is one of the soft skills that is expected to develop in senior high school students through the subjects of entrepreneurship (PKWU) in the 2013 curriculum in accordance with Permen 37 of 2018. These subjects are usually fostered by teachers in the fields of Chemistry, Biology, and Physics. The chairpuson of the Padang City MGMP chemistry teachers sent the letter to LP2M through chemistry department to give training enterpreneural material. This is due to the lack of chemistry entrepreneurship teaching materials in schools that can be used as a reference in the implementation of PKWU subjects. The solution offered is training in processing vegetable materials into economically valuable products as a form of entrepreneurship for Padang City MGMP chemistry teachers, so that they can help implement PKWU learning for chemistry teachers in schools. The Community Service Team of the Department of Chemistry FMIPA UNP has provided entrepreneurship-based applied chemistry training, particularly in the processing of vegetable materials into economically valuable products as a form of entrepreneurship for MGMP Chemistry teachers in Padang. The training provided is considered effective in improving the abilities and skills of MGMP Chemistry teachers in Padang City in processing vegetable materials into various economically valuable products. Chemsitry teachers can be applied in PKWU learning in senior high school. Vegetable materials used in this training are yam and corn, because the two vegetable materials are abundant and easily obtained in the city of Padang